REPRESENTASI SIKAP NASIONALISME DALAM SINEMA INDONESIA (Studi Peran Komunikasi Massa Modern Film “Darah dan Doa”) - Henricus Hans (Universitas Bunda Mulia, 2015)
Nationalism Indonesia was formed through a complex path with a relatively long time. An understanding of nationalism itself one of which can be understood through the medium of film. Here, a film as a product of modern art becomes a medium in conveying the message directed to the audience. Through the footage presented in a film, audiences are invited to enter a world that is commonly referred to